2022
DOI: 10.3389/fcvm.2022.990007
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 immunobiology in coronary artery disease: A systematic review and meta-analysis

Abstract: The IL-33/ST2 axis is reported to be controversially associated with coronary artery disease (CAD). A systematic review of the association between the IL-33/ST2 axis and CAD revealed that IL-33/ST2 plays a protective role in CAD and serum sST2 and IL-33 levels are increased in patients with cardiovascular disease. Therefore, the association of IL-33/ST2 single nucleotide polymorphisms (SNPs) with CAD prevalence, prognosis, and risk factors was assessed by performing a meta-analysis. Through a literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Focusing on the single nucleotide polymorphisms (SNPs) of IL-33 , we discovered a significant inverse association between IL-33 SNP rs3939286 and COVID-19 severity, which meant that carriers of the minor genotype were found to be protected from developing more severe forms of COVID-19. While the role of IL-33 SNPs in viral infections, particularly COVID-19, remains largely unexplored, previous studies have indicated a protective effect of this SNP in other diseases, such as rheumatoid arthritis and cardiovascular conditions [ 29 , 30 ]. It is plausible to suggest that rs3939286 may play a role in regulating IL-33 production and, subsequently, lowering the risk of developing severe disease in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the single nucleotide polymorphisms (SNPs) of IL-33 , we discovered a significant inverse association between IL-33 SNP rs3939286 and COVID-19 severity, which meant that carriers of the minor genotype were found to be protected from developing more severe forms of COVID-19. While the role of IL-33 SNPs in viral infections, particularly COVID-19, remains largely unexplored, previous studies have indicated a protective effect of this SNP in other diseases, such as rheumatoid arthritis and cardiovascular conditions [ 29 , 30 ]. It is plausible to suggest that rs3939286 may play a role in regulating IL-33 production and, subsequently, lowering the risk of developing severe disease in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on mouse depression showed (49) that the IL-33 gene is associated with mouse social stress (SS), and changes in mouse coronary blood flow, and that there is a link between MDD and coronary heart disease. Our prior study demonstrated that IL-33's immune regulatory role in CAD regulation is inconsistent, which may be due to the different biological roles of IL-33 as a cytokine and transcription factor (52). Hence, we hypothesize that IL-33's biological activity in acting as both a cytokine and transcription factor can influence the regulation of depression.…”
Section: Discussionmentioning
confidence: 92%
“…A subsequent study stressed the prognostic significance of IL-33 in patients after revascularized acute coronary syndrome, with higher levels indicating a higher disease complexity and poorer 1-year prognosis [76]. It should also be stated that although the IL-33/ST2 axis may be related to coronary atherosclerosis, the various gene single nucleotide polymorphisms may modify this association, as suggested by a recently reported systematic review and meta-analysis [77]. Other than its role in atherosclerosis, IL-33 exerts a protective effect in most infectious settings, by assisting the clearance of the causal microorganism [78].…”
Section: Il-1 Familymentioning
confidence: 96%